PENGARUH PUTUSAN DEWAN KEHORMATAN PENYELENGGARA PEMILIHAN UMUM TERHADAP HASIL PEMILIHAN GUBERNUR LAMPUNG 2014 - Aryo Fadlian (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
AbstractThe implementation process of the election of Governor of Lampung in 2014was still a lot of controversy with the process so complicated that ultimatelyresulted elected leaders, after the long process, sprang DKPP decisionrelating to the election of the Governor of Lampung in 2014. The verdict ofDKPP generates convicted and fired Lampung Provincial ElectionSupervisory Board The purpose of this research was to determine andanalyze the strength of decision DKPP Lampung gubernatorial election in2014. In this study the authors discussed the use of theory and concepts;theory of legislation, the concept of the State institutions, the concept of anindependent State institution using normative juridical research method, i.e.obtaining secondary data obtained from the study of literature, books, andlegislation. Results of research and discussion show that many violations inthe elections in 2014 that resulted in the governor of Lampung in 2014resulted in the termination of the Election Supervisory Board membersLampung province because it violates the code of ethics. Strength HonorCouncil Election decision final and binding give lessons to the electionorganizer Lampung Province.Keywords: Verdict Strength, Election Organizer Ethics Council, ElectionViolationsAbstrakProses pelaksanaan pemilihan Gubernur Lampung tahun 2014 masih banyakkontroversi dengan prosesnya yang begitu rumit sehingga akhirnyamenghasilkan pemimpin terpilih, setelah proses yang panjang, munculkeputusan DKPP terkait pemilihan Gubernur Lampung tahun 2014. Putusantersebut DKPP menghasilkan terbukti dan dipecat Badan Pengawas PemiluProvinsi Lampung. Tujuan dari penelitian ini adalah untuk mengetahui danmenganalisis kekuatan keputusan pemilihan gubernur DKPP Lampung padatahun 2014. Dalam penelitian ini penulis membahas penggunaan teori dankonsep; Teori perundang-undangan, konsep lembaga negara, konseplembaga negara merdeka yang menggunakan metode penelitian yuridisnormatif, yaitu memperoleh data sekunder yang diperoleh dari studi literatur,buku dan perundang-undangan. Hasil penelitian dan pembahasanmenunjukkan bahwa banyak pelanggaran dalam Pemilu 2014 yangmengakibatkan Gubernur Lampung pada tahun 2014 mengakibatkanpenghentian anggota Badan Pengawas Pemilu Provinsi Lampung karenamelanggar kode etik. Keputusan Kehormatan Dewan Kehormatan keputusanfinal dan mengikat memberi pelajaran kepada penyelenggara pemiluProvinsi Lampung.Kata Kunci: Kekuatan Putusan, Dewan Kehormatan PenyelenggaraPemilihan Umum, Pelanggaran Pemilu